THE TYPES OF JUMPS REQUIRED IN PHYSICAL EDUCATION AND SPORTS PRACTICE, THE PECULIARITIES OF JUMPING AND JUMPING ENDURANCE - Azizov Muhammadjon Azamovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article analyzes the processes of execution in a more and more scalable way, in which the types of jumps required in physical education and sports practice, jumpiness, and jumping endurance are distinguished by their characteristic features.